The comparition of Personality Patterns, irrational beliefs and impulsivity in males with with drug abuse disorder under Treatment - samere asadi; Majid Mahmod allilo; jafar bahadorikhosroahhi; maryam KHORSAND (Drug Control Headquarters, Research and Education Office, 2015)
Objective: the aim of this research was to determine the difference between personality Patterns, irrational beliefs and impulsivity in men with drug abuse disorder under Treatment. Method: in this casual- comparative research, 80 men ( 40 males with drug abuse under Treatment and 40 of normal males) that were selected with available sampling .Groups were matched in terms of demoghraphy characteristics ( age, sexuality, education level and marital status) and were valued with means of Eysenk Perceived Stress Inventory, Jonze Irrational Beliefs Scale and Baret Impulsivity Inventory. Results: The result of variance analysis showed that addicts compared to normal people, get more scores on extraversion, neuroticism and psychosis. Addicts group had Higher men scores in irrational beliefs compare of other group. There was significant difference between groups in impulsivity and impulsivity in addicts persons is the most. Conclussion: The traits of Personality, irrational beliefs and Unrealistic and high level impulsivity are factors that propel individuals toward more drug abuse and finally addict and aiming this factors in individuals with abuse disorder under Treatment can lead to prevent of Substance Abuse Relapse.